Circuito regional de performance BodeArte: encontros, coletividade e porítica na performance do Rio Grande do Norte - Bezerra, Andre Luiz Rodrigues (2014)
This dissertation aims to look into the structure of the event Circuito Regional de Performance BodeArte1 to think how it collaborate with its proposal providing theoretical points to relevant questions to the comprehension of Brazilian performance art in contemporaneity, since its conceptual format until its occurrence and practical limitations. From this proposition the dissertation is organized into three chapters guided for the following aspects: the resumption of the events encompassed on the occurrence of Circuit BodeArte as well as a tabulation of the data reunited in its history, the presentation of its conceptual choices, and the metaphors conducted by the use of the term performance and how they can lead us to the idea of a performance-as-BodeArte. The methodological structures moved for this organization are qualitative, and have been formed from printed materials, texts, festival programs, blog, videos, photos, interviews, lectures and forums, plus our own memory as a producer and performer of the event, looking through these set points of the epistemological organization contained on the proposal of the Circuito, expanding and discussing them. This way this research moves between the propositions of this event in its three editions, promoting discussions that dialogue with concepts such as the emergence of Steve Johnson (2004), the metaphors of thought proposed by Christine Greiner (2005), the idea of performance hacker of Maria Beatriz de Medeiros (AQUINO, et al., 2012), as well as other propositions presented by Jan Swidzinski (2005) and Eleonora Fabião (2012)